Relevance of muscle fibre typology in sports (PhD Academy Award) - Lievens, E. (British Journal of Sports Medicine, 2023)
What did I do? For 50 years, we have known that muscle fibre typology is an important characteristic for sports performance.1 Nevertheless, everyone seemed to have resigned themselves to the fact that the muscle fibre typology is not measurable and applicable in the daily guidance of athletes. I challenged this status quo, by successfully optimising a non-invasive method to investigate the muscle fibre typology and I applied this technique to find several new links between the muscle fibre typology and sport performance (fatigue and recovery, talent identification and injury susceptibility).